Personality, perceived appropriateness, and acknowledgement of social influences on food intake. (December 2015) - Spanos, Samantha; Vartanian, Lenny R.; Herman, C. Peter; Polivy, Janet
Abstract: Social influences are powerful determinants of food intake. Whereas some people are willing to acknowledge social influences on their food intake, others seem to actively deny being influenced by social cues. Across three samples (total n = 835), we examined factors that prior theory and research suggest might predict people's willingness to acknowledge social influences on their food intake. These included conformity, self-monitoring, sociotropy, self-esteem, empathy, and the Big Five personality traits. Conformity, self-monitoring, and sociotropy were the most consistent predictors of acknowledgement of social influences on food intake, and conscientiousness was also related to acknowledgement of social influences. Furthermore, those effects were mediated by the extent to which people believe that eating in response to social cues is appropriate. These findings suggest that people who are more concerned with, and attuned to, the social world are more willing to acknowledge being influenced by social factors. Importantly, individuals who are less willing to acknowledge social influences on their food intake may not actually be any less influenced by social cues. Failing to acknowledge social influences on food intake could have implications for people's ability to regulate their eating appropriately and also for their self-evaluations. Highlights: People vary in their acknowledgement of social influences on their food intake. Acknowledgement of social influences is related to certain personality traits. Relevant traits are conformity, self-monitoring, sociotropy, and conscientiousness. These associations are mediated by perceived appropriateness of social influences.